Evidence of multiple cellulase forms in Trichoderma harzianum E58 and their significance in cellulose hydrolysis. - Porter, Suzanne L. (University of Ottawa (Canada), 1990)
The occurrence of multiple cellulase components of Trichoderma harzianum E58 and the implications of their existence on the hydrolysis of cellulose were examined. A single commercial enzyme preparation, Novo-Celluclast, showed different extents of hydrolysis of several cellulosic substrates over time. The filter paper activities of six batches of T. harzianum E58 showed poor correlation with the ability of these enzymes to hydrolyze other cellulosic substrates over extended periods of time. Hydrolysis of a single substrate by a single enzyme preparation resulted in similar slopes in reducing sugar production with enzyme concentration, between one-hour and twenty-four-hour hydrolyses. The multiplicity of the cellulase components of T. harzianum E58 was examined, and the number of endoglucanase components and their specificities towards $\beta$-1,4-linkages were studied. Several types of endoglucanases were produced by the fungus. The role of the exoglucanase was examined using sub-saturation concentrations of T. harzianum E58 cellulase. No significant increase in hydrolysis was observed when purified exoglucanase was added to the cellulase mixture. The high proportion of non-specific endoglucanases and the need for an efficient endoglucanase-to-exoglucanase ratio are discussed in terms of a modified model for cellulose hydrolysis. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.